Computational studies evidenced the potential of steroidal lactone to disrupt surface interaction of SARS-CoV-2 spike protein and hACE2. (July 2022) - Yadav, Ajay; Ojha, Monu Dinesh; Hariprasad, P.
Abstract: The critical event in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pathogenesis is recognition of host cells by the virus, which is facilitated by protein-protein interaction (PPI) of viral Spike-Receptor Binding Domain (S-RBD) and Human Angiotensin Converting Enzyme 2-Receptor (hACE2-R). Thus, disrupting the interaction between S-RBD and hACE2-R is widely accepted as a primary strategy for managing COVID-19. The purpose of this study is to assess the ability of three steroidal lactones (SL) (4-Dehydrowithaferin A, Withaferin A, and Withalongolide A) derived from plants to disrupt the PPI of S-RBD and hACE2-R under two conditions (CON–I and CON-II) using in-silico methods. Under CON–I, 4-Dehydrowithaferin A destabilizing the interactions between S-RBD and hACE2-R, as indicated by an increase in binding energy (BE) from −1028.5 kJ/mol (control) to −896.12 kJ/mol 4-Dehydrowithaferin A exhibited a strong interaction with S-RBD GLY496 with a hydrogen bond occupancy (HBO) of 37.33%. Under CON-II, Withalongolide A was capable of disrupting all types of PPI, as evidenced by an increased BE from −913 kJ/mol (control) to −133.69 kJ/mol and an increased distance (>3.55 nm) between selected AAR combinations of S-RBD and hACE2-R. Withalongolide A formed a hydrogen bond with TYR453 (97%, HBO) of S-RBD, which is required for interaction with hACE2-R's HIS34. Our studies demonstrated that SL molecules have the potential to disrupt the S-RBD and hACE2-R interaction, thereby preventing SARS-CoV-2 from recognizing host cells. The SL molecules can be considered for additional in-vitro and in-vivo studies with this research evidence. Graphical abstract: Image 1 Highlights: The critical event in SARS-CoV-2 pathogenesis is recognition of host cells. Plant secondary metabolites are potential anti -COVID-19 agents. Withalongolide A and 4-Dehydrowithaferin A interact with S-RBD with high affinity. Steroidal lactones disrupt amino acid residue interactions between S-RBD-hACE2-R. Free binding energy between S-RBD and hACE2-R reduced by steroidal lactones.